Sistem Pendukung Keputusan Pemilihan Mitra Jasa Pengiriman Barang Menggunakan Metode Additive Ratio Assessment (ARAS) PT Raya Utama Travel - Wulan Ramadhani; Nelly Astuti Hasibuan; Rivalri Kristianto Hondro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
A decision support system is generally defined as a system capable of producing solutions and handling problems. Decision support systems are not intended to replace the role of decision makers, but to assist and support decision makers. Medan City is a big growing city, so it's no wonder there are so many shipping service partners that offer delivery services for the public. Where most of the shipping partners reach not only in Medan but also nationally and even internationally. Raya Utama travel is a travel agent that does not only serve flight and tour ticket sales. But it also serves passports and visas in various parts of the world, therefore every day it is necessary to send files for making these visas.